The Impact of Gold Price Volatility on MSMEs’ Access to Financing: A Systematic Literature Review - Hulaimi, Ahmad; Hidayanti, Nur Fitri (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This study aims to examine the relationship between fluctuations in gold prices and access to financing for MSMEs using a qualitative approach through a Systematic Literature Review (SLR).Methods: Data sources were obtained from various reputable scientific databases, such as Google Scholar, Scopus, ScienceDirect, and Web of Science, covering the publication period from 2015 to 2025, with a literature selection process adhering to the PRISMA guidelines.Results: The analysis results indicate that gold price fluctuations have a significant and asymmetric impact on SME access to financing. An increase in gold prices contributes to higher collateral values, greater borrowing capacity, and expanded credit access, whereas a decrease in gold prices leads to lower collateral values, increased credit risk, and restricted access to financing. These findings confirm that gold plays a strategic role as a financial instrument for SMEs. Nevertheless, research gaps remain, particularly regarding the integration of financial behavior analysis, the response of financial institutions, and the utilization of predictive models.Conclusion and suggestion: Future research should focus on developing technology-based approaches and innovative financing schemes that are adaptive and sustainable.